2011
DOI: 10.1016/j.rbmo.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sperm DNA fragmentation on the outcome of IVF with own or donated oocytes

Abstract: A prospective study was performed to assess the impact of sperm DNA fragmentation on the outcome of IVF with own or donated oocytes. The study population included 178 couples (62 cycles of IVF, 116 of intracytoplasmic sperm injection (ICSI)) with own (n=77) and donor (n=101) oocytes. DNA fragmentation was evaluated by TdT (terminal deoxynucleotidyl transferase)-mediated dUDP nick-end labelling assay. Correlation between DNA damage to oocyte fertilization, embryo quality and clinical pregnancy, implantation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 37 publications
5
42
2
1
Order By: Relevance
“…Though the relationship between sperm assessment and accurately diagnosing male infertility or predicting conception remains ambiguous [2,[21][22][23], semen analysis is the first diagnostic tool used to determine a contributing male factor in an infertile couple. Manual semen analysis, based largely on the evaluation of sperm concentration, motility and morphology, is known to suffer from lack of standardization, repeatability and accuracy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Though the relationship between sperm assessment and accurately diagnosing male infertility or predicting conception remains ambiguous [2,[21][22][23], semen analysis is the first diagnostic tool used to determine a contributing male factor in an infertile couple. Manual semen analysis, based largely on the evaluation of sperm concentration, motility and morphology, is known to suffer from lack of standardization, repeatability and accuracy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the prevalence of males with high levels of SDF is greater in the infertile than in the fertile population (Spano et al, 2000;Zini et al, 2002), and that many couples with unexplained infertility have higher levels of SDF (Host et al, 1999;Oleszczuk et al, 2013). However, studies examining the effect of high SDF on assisted conception fertilization, embryo development, pregnancy, miscarriage, and birth outcomes report conflicting results; some studies report a correlation between SDF and outcomes for both in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles (Collins et al, 2008;Robinson et al, 2012), others that IVF but not ICSI outcomes are influenced (Bungum et al, 2007;Zini, 2011;Osman et al, 2015), and others have found no clear association with either assisted fertilization method (Esbert et al, 2011;Ni et al, 2014). These inconsistencies may in part be attributed to study design and the use of different assays, with a recent study reporting that Comet and TUNEL assays were more predictive of clinical outcomes than SCSA (Simon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We found a very few number of study assessing the contrary. For example in [26] study, there were no correlation between DNA fragmentation and the issue of ART technique. But it is important to note the fact that in that study, the cases included oocyte donor (so young selected women with high quality oocyte).…”
Section: Discussionmentioning
confidence: 79%